2006
DOI: 10.1038/sj.cgt.7700951
|View full text |Cite
|
Sign up to set email alerts
|

FasL gene therapy: a new therapeutic modality for head and neck cancer

Abstract: In this study, we investigated the in vitro and in vivo efficacy of Fas ligand (FasL) gene therapy for the treatment of head and neck cancer. Three head and neck squamous cell carcinoma (HNSCC) cell lines (SCC-1, SCC-12, and SCC-14a) were treated with the Fas agonist CH-11, a monoclonal antibody to the Fas receptor, or with a replication-incompetent adenovirus (AdGFPFasL) expressing a modified murine Fas ligand gene fused to green fluorescent protein (GFP). A replication-incompetent adenovirus containing the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…It was a pleasant surprise to see that apoptotic vesicles maintained a FasL-directed killing mechanism in most prostate cancer and control cell lines. We have subsequently demonstrated that this approach also works in a similar fashion in head and neck cancer cell lines of squamous cell origin, 18 and in human renal cancer cells. 19 …”
Section: Eliciting Bystander Activitymentioning
confidence: 80%
See 2 more Smart Citations
“…It was a pleasant surprise to see that apoptotic vesicles maintained a FasL-directed killing mechanism in most prostate cancer and control cell lines. We have subsequently demonstrated that this approach also works in a similar fashion in head and neck cancer cell lines of squamous cell origin, 18 and in human renal cancer cells. 19 …”
Section: Eliciting Bystander Activitymentioning
confidence: 80%
“…The mechanism of resistance lies in part with the observation that tumor cells frequently upregulate genes involved in inhibition of apoptosis, including FLIP s , 22 Survivin and cIAP1. 18,[22][23][24][25] This led to the concept discussed below, in which FasL gene therapy is combined with agents that downregulate the anti-apoptotic phenotype of tumors creating a more pro-apoptotic phenotype which facilitates bystander activity. This has already been tested in prostate tumor xenograft using TRAIL, Apoptin and FasL [23][24][25] and in head and neck xenografts (unpublished).…”
Section: Resistance To Bystander Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…AC is a ratelimiting enzyme that converts ceramide to sphingosine; activity of AC and of sphingosine kinase establishes the ratio between the cellular concentrations of ceramide, sphingosine, and sphingosine-1-phosphate that eventually determine whether a cell will die or enter the antiapoptotic pathway (12,13). Because of its role as an apoptotic regulator, AC is vital in early embryonic development, as demonstrated recently by Eliyahu et al (8).…”
mentioning
confidence: 86%
“…The Fas/FasL apoptotic pathway has been considered a critical mechanism for eliminating tumor cells. It was previously demonstrated that FasL was required for curcumin-induced apoptosis in Huh7 cells (40), and the Fas/FasL pathway contributed to the antitumor effects of a combination therapy of interferon (IFN)α and 5-fluorouracil (5-FU) against HCC cells (41), and intratumoral injections of an adenovirus expressing FasL gene into the HNSCC (head and neck squamous cell carcinoma) cell xenografts induced significant growth suppression of tumors (42). Combining these reports and our experimental results, as well as the role of EGR3 in transactivation of the FasL promoter in certain cell types (35,36), we speculate that EGR3 may also promote FasL expression, and FasL is related to the EGR3-mediated cell growth inhibition in HCC cells.…”
Section: Discussionmentioning
confidence: 99%